Transformation of Student Interpersonal Communication Through Digital Media in Higher Education - Maya Masyita Suherman; Tuti Alawiyah; Luna Nuranisa Zakiah (Universitas PGRI Yogyakarta, 2026)
This research aims to explore the challenges and strategies for successful student interpersonal communication in the digital era, particularly focusing on digital platform usage for academic and social purposes. Information technology development has fundamentally transformed student interaction patterns, where text-based communication and social media have replaced many face-to-face interactions. Using a quantitative survey method with 200 active students, this study found that social media usage intensity positively correlates with digital misunderstanding levels. In contrast, face-to-face communication significantly contributes to interpersonal relationship satisfaction. Thematic analysis of qualitative data revealed student strategies including message clarification, emoji utilization, and switching to video platforms to overcome digital communication barriers. Furthermore, excessive social media use can trigger social anxiety and isolation feelings. These findings indicate that while digital platforms enhance efficiency and collaboration, they also risk communication quality and mental well-being, necessitating balanced approaches and improved digital communication literacy among students in higher education. Keywords: interpersonal communication, digital platforms, social media, social life